Heleny Modrzejewskiej intymny zapis roli odgrywanej na scenie życia. Kilka przyczynków .......... 11 („Szalony, kto nie chce wyżej, jeżeli może”: Studia i materiały do badań nad życiem i twórczością Heleny Modrzejewskiej, 2025)
MODJESKA’S INTIMATE RECORD OF THE PART PLAYED BY HER ON THE LIFE STAGE: A FEW INSIGHTSThe article is an attempt to see how far it is possible to identify and interpret emotions behind incidental personal records Modjeska made in special moments of her life. The analysis covers the notes that the actress’ daughterin-law Felicja put in her 1929 edition of Wspomnienia i wrażenia (Memoires and Impressions) by Modjeska. It was checked which of them Helena included in the her authorized version of Memoires and Impressions, published in New York in 1910.